Transição agroecológica em sistemas de produção de batata - Fioreze, Claudio (2005)
This work was done as an articulation program between technicians of EMATER-RS, UFSM and FEPAGRO-RS and small farmers of ASBAT. The research aimed to evaluate management practices of the potato production in a systemic approach to increase the environmental and partner-economic sustainability for small farmers and for alimentary security of the southern region do Brazil. The scientific paradigm of the agroecological transition was adopted, breaking itself of the conventional system - which is widely dominant in Brazil - for the development of systems with increasing sustainability. The main studies had been concentrated in two systems of production: I spring season crop and II fall season crop, composed of subsystems of crop rotation (with commercial cultures and soilcover crops), of fertilization (organic, mineral or both) and crop protection management and harmful plants. The main objective of the work was to evaluate and develop these systems, especially the agroecological potato production system, from the efficacy of organics manures usage and practical available alternatives. This management should result in improvements of soil, products and environment quality with greater yield. The main experiment was carried out at FEPAGRO in Júlio de Castilhos - RS. Complementary experimental units were conducted small farms. The methodology, results and conclusions of the complementary studies are in Appendices. The general results allow preliminarily conclusions that it is viable for potatoes farmers to use organics fertilizers or in combinations with mineral fertilizers. In the experimental conditions, the disease control with pesticides was not necessary for potato. Insect control of soil-insect plagues consists in a serious impediment to implement the production system, because of no efficacy of the studied plant extracts. There was no impact in the potato quality, specially the physical and chemical soil properties, implying that the effects of the environmental and economic impact of organic fertilization, ecological control and covering plants can be correctly measured in long term experiments. Therefore, continuing increasing complexity of these studies are necessary in the future to keep potato production in small farms.